Analisis Penentuan Parameter Gempa Untuk Perhitungan Stabilitas Bendungan - Hidayawan, Ahmad; Kurniawan, Andri; Adhi, Bagas Wahyu; Setiyanto, Beni; Rahayu, Hayu (Media Komunikasi Dunia Ilmu Sipil (MoDuluS), 2024)
Dams have an important role in controlling floods and providing water supply for infrastructure and community needs. The construction of the Pidekso Dam, as part of government efforts, requires research to determine earthquake parameters to ensure the safety of its structure. Pidekso Dam, located in the downstream Bengawan Solo river, is prone to earthquakes because it is adjacent to areas where earthquakes often occur. This study aims to determine the parameters of the earthquake coefficient Operating Basis Earthquakeee (OBE) and MaximumaDesignaEarthquakee (MDE) based on the 2017 earthquake map of Indonesia. Analysis was conducted to assess the risk of dam collapse due to earthquakes. Based on the dam risk class criteria, Pidekso Dam has a high risk class with a total weight of 30. For OBE earthquake analysis, the earthquake coefficient used ranges from 0.1 to 0.15 g, with a probability of being exceeded by 2% in 100 years. As for MDE earthquakes, the earthquake coefficient ranges from 0.5 to 0.6 g, with a repeat period T = 5000 years.